KEBIJAKAN KRIMINALISASI TERHADAP PELAKU TINDAK PIDANA PEDOFILIA MENURUT HUKUM PIDANA INDONESIA - Vicky Khoila Winarto; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Pedophilia is a sexual disorder in the form of desire or fantasies of sexual impulses involving minors. In Indonesia the crime of pedophilia by the Criminal Code Article 289, Article 290 and Article 293 of molestation. While pedophilia is an extraordinary crime that should be regulated more specifically in the legislation such as the law on pedophilia. Based on this understanding, the author of this scripts formulated two formulation of the problem, namely: First, How are the criminal acts of pedophilia under Indonesian criminal law? Second, Is the setting on the crime of pedophilia in accordance with the theory of criminalization?The research method in this study, First, this kind of research is legal normative and descriptive analysis. Second, the data source supported by the source of the primary data, secondary data, and the data tertiary. Third, data collection techniques used is the study of literature. After the data collected then analyzed qualitatively, and concludes with the deductive method of thinking is to analyze the problems of the general form into special shapes.From the research problem there are two main things that can be inferred, first, setting the crime of pedophilia by the Indonesian Penal Code refers to criminal punishment for sexual crimes, such as sexual harassment or molestation. When referring to an explicit definition of pedophilia in Indonesian positive law, ie, pedophilia is defined obscenity. Act No. 35 of 2014 on the Amendment Act No. 23 of 2002 regarding Child Protection. Second, regulation of the crime of pedophilia by the criminalization policy which can not be removed from the crime prevention goals. Sanctions against perpetrators of crime should be given special sanction to deter such sanctions pengkebirian and also in prevention efforts with non penal policy. The obligation of governments to prudently adjust what was defined as a criminal act with a sense of law in the society.Based on this, Indonesia should make further rules regarding the crime of pedophilia into a form of legislation such as the laws on pedophilia and weighing punitive sanction against criminal castrate pedophiles.Keywords : Criminalization –Criminal Act - Pedophilia